Crenological Features of the Świętokrzyskie Voivodeship - Zieliński, Artur; Choiński, Adam (Bulletin of Geography. Physical Geography Series, 2022)
On the basis analysis of 53 hydrographic maps in the scale 1:50,000, an inventory of crenological objects in the Świętokrzyskie Voivodeship was made. A total of 462 of them were identyfied. Most of them are permanent springs, precisely 346, followed by: 60 permanent springs with intakes, then 34 periodic springs, 10 spring groups, 5 bog springs, 3 mineral springs, 3 observed springs and 1 other outflow. Moreover, the studies revealed the diversity and specificity of the region in terms of crenology. Total discharge of all springs is small as it was estimated at 459.04 dm3•s–1. The most efficient springs reach about 40 dm3•s–1 and only eight exceed 20 dm3•s–1. The total discharge of the 10 most efficient outflows amount to 258.6 dm3 s-1, which accounts for 56.3% of the output in the Świętokrzyskie Voivodeship. In terms of the number of crenological objects, there is a clear difference between the mountain and highland identyfied. In the area of the Świętokrzyski National Park, 25 outflows were registered. Their total output is 6.5 dm3•s–1. At the same time, on the northern slopes of the Świętokrzyski National Park, 21 crenological objects with a total discharge of 5.5 dm3•s–1 were identyfied.